Utilization of Plants as Natural Dyes for Ikat Woven Clothes of The Kemak Tribe In Dualaus Village, Kakuluk Mesak District, Belu Regency: Pemanfaatan Tumbuhan sebagai Pewarna Alami Kain Tenun Ikat Desa Dualaus Kabupaten Belu - Naisumu, Yolanda Getrudis; Nascimento, Cidalia Pires Do (Jurusan Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Timor, 2025)
Indonesia is a country with high biodiversity. High biodiversity has great potential in providing raw materials from nature and has abundant natural resources. The purpose of this study was to determine the types of plants used as natural dyes for the Kemak Tribe's ikat woven fabrics in Dualaus Village, Kakuluk Mesak District, Belu Regency. This research was conducted in Dualaus Village, Kakuluk Mesak District, Belu Regency from March to July 2024. This study used qualitative and quantitative descriptive research methods. Based on the results of interviews in Dualaus Village, Kakuluk Mesak District, Belu Regency, data was obtained that there are 11 types of plants used by the community in the process of dyeing ikat woven fabrics, including soga (Peltophorum pterocarpum) katuk (Souropus androgynus), tarum (Indigofera tinctoria L.), ketapang (Terminalia catappa) kusambi (Schleichera oleosa), butterfly flower (Oxalis triangulalis), kudo (Lannen coromandelica), and mahogany (Swietenis mahagoni). turmeric (curcuma domestica L.) beluntas plant (Pluchea indica L.), hibiscus (Hibiscus rosa-sinensis L.). The parts of the plant used are bark, leaves, flowers and rhizomes. The parts of the plants taken are processed traditionally in 2 ways, namely boiled and pounded, the colors produced are soga, tarum and katuk produce black, ketapang produces dark brown, kusambi produces cream, butterfly flowers produce light cream, kudo produces caramel brown, mahogany produces light brown, soga and turmeric rhizomes produce yellowish brown, beluntas leaves produce dark cream, hibiscus produces greenish cream, turmeric and beluntas rhizomes produce brownish yellow, turmeric rhizomes produce yellow. The conclusion is that there are 11 types of plants used in Dualau Village and the parts used to produce color are bark, leaves, flowers and rhizomes.